We had to take it : the Kishorn story. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1980)
An inspection of the community of Kishorn and the effect that oil had. This is then used to show possible consequences of oil development in Newfoundland. Tracking is very bad (beginning of video, which was cropped, said May 1979)